Shakespeare and continental philosophy - Bates, Jennifer Ann, 1964-; Wilson, Richard, 1950- (Edinburgh University Press, 2014)
This collection of 15 essays by celebrated authors in Shakespeare studies and in continental philosophy develops different aspects of the interface between continental thinking and Shakespeare's plays. The authors draw from current continental philosophy (e.g. Lacan, Foucault, Derrida) as well as from the 19th century continental tradition (e.g. Hegel, Kierkegaard) and from the early roots of continental tradition (e.g. Aristotle, Ibn Sina). The chapters address the span of the tragedies, comedies and history plays in the light of thinkers as diverse as Aristotle, Ibn Sina and Jean-Luc Marion, Hegel, Kierkegaard, Schopenhauer, Schmitt, Arendt, Lacan, Levinas, Foucault and Derrida.--Provided by publisher.